CCAFS’ influence and reach in motivating actors globally to tackle climate change reaching 60 million people - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS’ science, engagement with strategic partners and capacity strengthening approach has globally i) shifted the debate on climate adaptation among strategic partners, with the program’s ideas having reached nearly 60 million people, ii) inspired positive change in government policy, with nearly 100 policy wins in just the two years up to 2019, iii) built a global community for climate adaption within a network of more than 60 thousand entities and iv) sparked public interest in CSA.